ASSESSMENT OF RISKS AND THEIR IMPACT ON THE LIFE CYCLE OF SOFTWARE DEVELOPMENT - LISHCHYNA, NATALIYA; BOIKO, LEV; HULCHUK, YURII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Modern software development is accompanied by numerous challenges associated with risks at all stages of the product lifecycle: from design and development to operation and support. Risks in software development can include technical (technological obsolescence, unstable requirements), managerial (insufficient communication, limited budget), and operational (errors, failure to meet user expectations). These risks directly affect the quality, timing, and budget of development, as well as the overall competitiveness of the software. Risk assessment and management are among the key scientific and practical tasks aimed at ensuring the efficiency of software development and implementation. This article analyzes the main risks that arise at different stages of the software development life cycle and presents modern methods of their identification and management. The author explores the risks associated with planning, requirements analysis, design, development, testing, implementation, and support of software products. The author identifies specific risks for each stage and suggests ways to minimize them. The article discusses in detail the main groups of risks that may arise at different stages of software development: planning, requirements analysis, design, development, testing, implementation, and support. Various methods of risk assessment are considered, such as decision tree analysis, forecasting, risk matrices, the Five Whys technique, and SWOT analysis. Effective methods of risk management are presented, including resource reservation, improved communication, staff development, use of flexible development methodologies (Agile, Scrum), and others. The paper emphasizes the importance of an integrated approach to risk management, which includes both the identification and assessment of risks and the development of effective strategies to minimize them. The methods and approaches proposed in the article can be used by project managers, developers, and other stakeholders to improve the efficiency of software development and reduce the risk of project failure.